Defeating Memory Corruption Attacks via Pointer Taintedness Detection - Chen, Shuo; Xu, Jun; Nakka, Nithin; Kalbarczyk, Zbigniew; Iyer, Ravishankar K. (Proceedings of IEEE International Conference on Dependable Systems and Networks, 2005)
Most malicious attacks compromise system security through memory corruption exploits. Recently proposed techniques attempt to defeat these attacks by protecting program control data. We have constructed a new class of attacks that can compromise network applications without tampering with any control data. These non-control data attacks represent a new challenge to system security. In this paper, we propose an architectural technique to defeat both control data and non-control data attacks based on the notion of pointer taintedness. A pointer is said to be tainted if user input can be used as the pointer value. A security attack is detected whenever a tainted value is dereferenced during program execution. The proposed architecture is implemented on the SimpleScalar processor simulator and is evaluated using synthetic programs as well as real-world network applications. Our technique can effectively detect both control data and noncontrol data attacks, and it offers better security coverage than current methods. The proposed architecture is transparent to existing programs.